A cross-comparative international study on the concept of wisdom. (September 2014) - Sánchez-Escobedo, Pedro; Park, Kyubin; Hollingworth, Liz; Misiuniene, Jurga; Ivanova, Liena
The article aims to depict the most common ideas regarding wisdom from young people across different countries: Latvia, Lithuania, Mexico, Republic of Korea and the United States. A questionnaire was administered to nearly 800 adolescents from these countries and comparisons by country and gender were made regarding participants' perceptions of a wise man and a wise woman. Although differences were found between countries, more consistent differences by gender were reported. From a global perspective, factor analysis established three major traits to describe wise people: charismatic, goal oriented and unconventional. Also, participants consistently excluded a person from the concept of wise if they were poor, pessimistic, naïve or inconsistent. Results indicate a lack of values attached to the description of wisdom and it is argued that schools should foster the development of conceptions of wisdom as a desirable stage in human development that includes values such as justice, equity and respect for others. Difficulties in international comparative research are discussed.